Problems of updating the Investment atlas of a subsoil user with reliable information on metallic and non-metallic mineral resources - A. P. Vasylenko (Мінеральні ресурси України)
Due to the difficult economic situation, which results in insufficient geological exploration, the rate of reproduction of the mineral resource base does not meet the needs of the state. There continues to be a significant reduction (and even absence) of budget funding and a significant decrease in the volume and types of exploration work for almost all types of minerals. The existing problems raise the issue of wider involvement of private investors not only in the extraction of minerals, but also in their exploration. To provide potential investors with information on the existence of investment objects, the State Service of Geology and Subsoil of Ukraine has introduced an investment atlas of subsoil users, which is one of the elements of the overall government policy aimed at attracting investors, including foreign ones. A typical profile of each object included in the investment atlas contains a general description of the site, coordinates, estimated resources, preliminary cost, minimum requirements for the work programme, as well as links to the deposit passport and relevant reports on the site. The data does not take into account the reassessment (monitoring) of the resource potential of metallic and non-metallic minerals that has been carried out in recent years. Based on the results of these works, the database of prospective and inferred resources was significantly changed. Many sites that did not meet the current environmental, economic and technological conditions were removed from the database. Given the risks that investors take when concluding a geological exploration contract, the reliability of the geological information underlying the assessment of prospective resources is crucial in making investment decisions. It is recommended that when updating the investment atlas with data on objects with defined resources, not only information from geological reports should be taken into account, but also the results monitoring.